Interfacial control of multiphase fluids in miniaturized devices - Priest, C.; Sedev, Rossen (2017)
© 2015 by Taylor and Francis Group, LLC. Interactions of solid surfaces with droplets, streams, and films of liquid occur in a wide variety of natural processes and are exploited in countless industrial processes and commercial devices. These surfaces, however, are generally heterogeneous, rough, or designed to be structured, and exhibit a diversity of wetting behaviors. At the microscale, these wetting interactions may dominate the other forces acting on the liquid phase, making them central to many microfluidic applications. The focus of this chapter is the interplay of geometry and chemistry in determining wetting behavior and the implications for passive control of fluids in microfluidic systems where immiscible fluids meet.